2012
DOI: 10.1063/1.4729903
|View full text |Cite
|
Sign up to set email alerts
|

Scanning transmission X-ray microscopy and X-ray absorption near-edge structure studies of N-doped carbon nanotubes sealed with N2 gas

Abstract: N-doped carbon nanotubes (NCNTs) were synthesized and their electronic structures have been explored by X-ray absorption near-edge structure (XANES) spectroscopy. With a surface sensitive mode, XANES confirms the N-doping in NCNTs. However, with a more bulk sensitive detection mode of XANES, large amount of gaseous N2 have been found to be sealed in NCNTs, even in a high vacuum environment. The encapsulation of the ferrocene residues in carbon nanotubes had been revealed by scanning transmission X-ray microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…N‐doped carbon nanotubes with excellent properties were widely used in fuel cells with excellent performance. Recently the electronic structures of NCNTs were explored by XANES . CNTs and NCNTs synthesized with the floating‐catalyst chemical vapor deposition method under similar conditions were studied by XANES in details .…”
Section: Carbon Nanostructures In Energy Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…N‐doped carbon nanotubes with excellent properties were widely used in fuel cells with excellent performance. Recently the electronic structures of NCNTs were explored by XANES . CNTs and NCNTs synthesized with the floating‐catalyst chemical vapor deposition method under similar conditions were studied by XANES in details .…”
Section: Carbon Nanostructures In Energy Applicationsmentioning
confidence: 99%
“…The electronic structure difference revealed by the XANES spectra provided strong evidence to understand the enhanced ORR performance. Also in a recent report XANES measured by a surface sensitive mode (TEY) was used to confirm N‐doping in NCNTs . NCNTs were synthesized by CVD method which might introduce gaseous N 2 in the system.…”
Section: Carbon Nanostructures In Energy Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong changes due to the expansion/contraction of the lattice and the mobility of silica species were observed, just as in TEM studies of Cu/ZnO catalysts (Figure 16,6a), nanofibre growth over Ni‐particles (Figure 18,6b) and oxidation/reduction of SOFCs (Figure 19,111). A recent study of RuO 2 on MWCNTs has further demonstrated that spectroscopic insight into changes in valence state can be obtained on the nm scale121 and the technique is attractive for studies of CNTs in general 122. The STXM approach was further applied to zeolite materials at work123 while Meirer at al 124.…”
Section: Towards Spatial Information On the Meso‐ To The Micro‐scalementioning
confidence: 99%